On the determination of battery energy storage capacity and short-term power dispatch of a wind farm - Li, Q.; Choi, San Shing; Yuan, Y.; Yao, D. (The Institute of Electrical and Electronic Engineers (IEEE), 2011)
A methodology on the design of a wind farm battery energy storage system to realize power dispatchability is described. Based on the statistical long-term wind speed data captured at the farm, a dispatch strategy is proposed which allows the battery capacity to be determined so as to maximize a defined service lifetime/unit cost index of the energy storage system. Also, the application of the dispatch strategy is shown to yield the short-term wind farm output power schedule which meets the specified confidence level of power delivery commitment. © 2010 IEEE.